Values held by Swedish primary school students towards forest ecosystems and the relevance for a nature's contributions to people approach. Issue 1 (1st January 2019) - Goodwin, Sean; Brogaard, Sara; Krause, Torsten
ABSTRACT: How the concept of value is defined within ecosystem services operates as a filter through which important ecosystem features are identified by the specific benefits they provide to society and individuals. This value narrative reflects intrinsic and instrumental concepts which have been challenged by the Nature's Contributions to People approach in additionally highlighting the importance of relational values, stemming from socio-cultural and ethical dimensions of human relationships with nature and ecosystems. Perceived as important for the interface between ecosystems and society, relational values are yet to be operationalised in ecosystem assessment processes. This study addresses how this can be done by using a mixed-method approach encompassing quantitative and qualitative data and methodologies. Our study focuses on how school children aged 10–12 years in Sweden (n = 403) value forest ecosystem services, and further hints at the contextual factors that mediate their value perception. Children are an important demographic for reasons of intergenerational equity, and because of the temporal inertia of intensively managed forest ecosystems in Sweden. Our results show that students display complex notions of value encompassing intrinsic, instrumental and relational values alike, highlighting the importance of a broader discussion on the valuation of ecosystems through mixed methods approaches.